A multi-scale computational approach based on TMS experiments for the assessment of electro-stimulation thresholds of the brain at intermediate frequencies. (9th November 2018) - Soldati, Marco; Mikkonen, Marko; Laakso, Ilkka; Murakami, Takenobu; Ugawa, Yoshikazu; Hirata, Akimasa
Abstract: In recent years, human exposure to electromagnetic fields (EMF) at intermediate frequencies (300 Hz–10 MHz) has risen, mainly due to the growth of technologies using these fields. The current safety guidelines/standards defined by international bodies (e.g. ICNIRP and IEEE) established basic restrictions for limiting EMF exposure. These limits at intermediate frequencies are derived from threshold values of the internal electric field that may produce transient effects, such as the stimulation of the nervous system. However, there are some discrepancies between the basic restrictions of those guidelines/standards. The aim of this study is to investigate the excitation thresholds of the nervous system exposed to intermediate-frequency electromagnetic fields, with the purpose of extrapolating the threshold-frequency curves which are compared with existing basic restrictions prescribed by the international guidelines/standards. Our investigation was based on transcranial magnetic stimulation (TMS) experiments, physiological measurements, and individualized MRI-based computer simulations for the determination of brain stimulation thresholds. The combined approach with established biological axon models enabled the extrapolation of the measured thresholds for sinusoidally varying electric fields. The findings reveal that the exposure limits are significantly conservative for the brain, especially at frequencies in the range of 300 Hz–5 kHz.